Strategic Choices for Social Responsibility of Startups in China - Liu, Bojing; Lu, Lu; Zhang, Hua; Liu, Chanjuan (Frontiers in Psychology, 2021)
This study uses the structure–conduct–performance analytical framework in industrial organization theory to analyze china startups’ corporate social responsibility (CSR) assuming normalization of the COVID-19 pandemic. Specifically, we take the external impact of startups during the pandemic as a starting point for analyzing the changes in the structure of startups and their CSR performance; we find a positive correlation between the pandemic and their performance. We aim to further elaborate that the CSR of startups is not simply altruism but must be an “altruistic and self-interested” mechanism. Therefore, this study proposes that during the pandemic, startups need to rebuild the CSR model. Furthermore, the company’s “economic man” and “social man” are interdependent; economic, ethical, and legal responsibilities are parallel; and charitable responsibilities remain the highest pursuit amid the pandemic. The social responsibility of startups as the COVID-19 pandemic normalizes is a strategic choice.